1991
DOI: 10.1007/bf00183458
|View full text |Cite
|
Sign up to set email alerts
|

Coordination geometry for cadmium in the catalytic zinc site of horse liver alcohol dehydrogenase: studies by PAC spectroscopy

Abstract: Active site substituted Cd(II) horse liver alcohol dehydrogenase has been studied by Perturbed Angular Correlation of Gamma rays Spectroscopy during turnover conditions for benzaldehyde and 4-trans-(N,N-dimethylamino)cinnamaldehyde. The ternary complex between alcohol dehydrogenase NAD+ and Cl-, and the binary complex between alcohol dehydrogenase and orthophenanthroline have also been studied. The Nuclear Quadrupole Interaction parameters have been interpreted in terms of different coordination geometries for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
62
0

Year Published

1994
1994
2011
2011

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(63 citation statements)
references
References 16 publications
1
62
0
Order By: Relevance
“…Spectroscopic studies of cadmium, copper, or cobalt substituted alcohol dehydrogenase in several instances have been taken to provide evidence for the presence of a fivecoordinated catalytic metal site [18][19][20]. The present results indicate that, to the extent that five-coordinate complexes do form with metal-substituted enzyme, this is likely to reflect the disparity in coordination preferences of different metal ions and cannot be taken to suggest that the catalytic metal site in native enzyme is five-coordinate.…”
Section: Comparison With Experimentsmentioning
confidence: 60%
See 1 more Smart Citation
“…Spectroscopic studies of cadmium, copper, or cobalt substituted alcohol dehydrogenase in several instances have been taken to provide evidence for the presence of a fivecoordinated catalytic metal site [18][19][20]. The present results indicate that, to the extent that five-coordinate complexes do form with metal-substituted enzyme, this is likely to reflect the disparity in coordination preferences of different metal ions and cannot be taken to suggest that the catalytic metal site in native enzyme is five-coordinate.…”
Section: Comparison With Experimentsmentioning
confidence: 60%
“…On the other hand, there is also strong crystallographic and spectroscopic evidence showing that binding to zinc of certain bidentate inhibitors is fivecoordinate [18][19][20]. Furthermore, spectroscopic studies of metal-substituted alcohol dehydrogenase have indicated that several binary and ternary complexes may be fivecoordinate [11][12][13][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…Yet, all experimental evidence (crystallographic and spectroscopic) agrees on that the free enzyme in the open conformation is four-coordinate [2][3]10,16,[19][20][21][22]44 . Further, it is widely assumed that the dehydration of the active site that occurs when the enzyme closes is important for the catalytic mechanism 1,2 .…”
Section: The Relative Stability Of Four-and Five-coordinate Zinc Compmentioning
confidence: 99%
“…Crystallographic and spectroscopic data showing that binding to zinc of certain bidentate inhibitors is fivecoordinate 14,15 have been taken as evidence in favor of these suggestions. Furthermore, spectroscopic studies of metal-substituted alcohol dehydrogenase have indicated that several binary and ternary complexes may be five-coordinate [6][7][8][15][16][17][18][19][20] , although other spectroscopic investigations contradict these results [21][22][23][24][25] . The kinetic evidence is also scattered and has been taken to favor fourcoordination 1,26 , as well as five-coordination 6,7,9,11,27 , of zinc in the catalytically productive ternary complexes.…”
Section: Introductionmentioning
confidence: 99%
“…This residue has been suggested to be involved in catalysis, either as a structural residue to stabilize the geometry of the active site (12), as a moderator of the electrostatic potential near the substrate (13), or, alternatively, as a possible zinc ligand during the enzyme's catalytic cycle (14)(15)(16). A recent atomic resolution structure of LADH in complex with NADH and Zn provides some evidence for different positions of the zinc-bound water and alternative conformations for Glu-68, indicating its potential as a zinc ligand (17).…”
mentioning
confidence: 99%